2010
DOI: 10.1161/circresaha.109.215392
|View full text |Cite
|
Sign up to set email alerts
|

Nox4 is a Novel Inducible Source of Reactive Oxygen Species in Monocytes and Macrophages and Mediates Oxidized Low Density Lipoprotein–Induced Macrophage Death

Abstract: Rationale: The enhanced formation of intracellular reactive oxygen species (ROS) induced by oxidized low-density lipoprotein (OxLDL) promotes macrophage death, a process likely to contribute to the formation of necrotic cores and the progression of atherosclerotic lesions. Yet macrophage deficiency of phagocytic NADPH oxidase (Nox2), the primary source of ROS in macrophages, does not reduce atherosclerotic lesion development in mice. This suggests an as yet unidentified NADPH oxidase may be present in macropha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
132
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 147 publications
(139 citation statements)
references
References 50 publications
(59 reference statements)
5
132
1
Order By: Relevance
“…We showed that in mice the chemotactic activity of monocytes increases with rising levels of hyperglycemia and hyperlipidemia and is associated with increased macrophage recruitment and accelerated atherosclerotic lesion formation (18). We further demonstrated that metabolic stress induces the expression of Nox4, an inducible Nox family member that we identified in monocytes and macrophages (19) and which plays a critical role in monocyte priming by metabolic stress (17). The aim of this study was to elucidate the mechanisms underlying the conversion of monocytes into this hypermigratory, proatherogenic phenotype induced by metabolic stress and to identify the redoxsensitive pathways targeted by Nox4-derived ROS in primed monocytes.…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…We showed that in mice the chemotactic activity of monocytes increases with rising levels of hyperglycemia and hyperlipidemia and is associated with increased macrophage recruitment and accelerated atherosclerotic lesion formation (18). We further demonstrated that metabolic stress induces the expression of Nox4, an inducible Nox family member that we identified in monocytes and macrophages (19) and which plays a critical role in monocyte priming by metabolic stress (17). The aim of this study was to elucidate the mechanisms underlying the conversion of monocytes into this hypermigratory, proatherogenic phenotype induced by metabolic stress and to identify the redoxsensitive pathways targeted by Nox4-derived ROS in primed monocytes.…”
Section: Discussionmentioning
confidence: 55%
“…S4) therefore may be an underestimation of total MKP-1 degradation triggered by metabolic stress. Increasing Grx1 activity also protected monocytes from converting into the hyperadhesive ( Metabolic stress in monocytes induces Nox4 (17), an inducible NADPH oxidase (Nox) family member we identified in monocytes and macrophages (19), and thereby promotes the S-glutathionylation of actin (17). To examine whether Nox4-derived ROS also mediate the S-glutathionylation, inactivation, and degradation of MKP-1, THP-1 monocytes were transfected with siRNA directed against Nox4 and then were exposed to metabolic stress, i.e., LDL plus high glucose.…”
Section: Metabolic Stress Promotes S-glutathionylation and Subsequentmentioning
confidence: 92%
See 1 more Smart Citation
“…Treatment of endothelial cells with NOX4 siRNA decreased LPS induced migration and adhesion of monocytes by 36% and 52%, respectively (335). Increased NOX4 activity is also a reported risk factor in the progression of type-2 diabetic nephropathy, stroke, pulmonary fibrosis, and atherosclerotic lesions (11,145,219,240,331,382). However, the contradictory reports in the literature suggest that NOX4 is a vascular protective enzyme rather than a destructive one (415).…”
Section: A Nadph Oxidase-derived Ros In Inflammationmentioning
confidence: 99%
“…NADPH oxidases are expressed in monocytes, macrophages, and cells of the vasculature 33. NOX1 and NOX4 are expressed in the walls of the vasculature, whilst NOX2 and NOX4 are present in endothelial cells 34.…”
Section: Diabetes and Cardiovascular Diseasementioning
confidence: 99%